Effective reading - Greenall, Simon; Swan, Michael; Nguyễn Trung Tánh; Nguyễn Trí Lợi; Trương Hoàng Duy; Phạm Tấn Quyền; Nguyễn Minh (Tp.HCM : Nxb Tp.HCM, 1997)
People and personalities; Food and drink; Houses and safety at home; Jobs and employment; Shopping, consumer affairs, advertising; Travel; Wildlife and the environment; Medicine and physical condition...
Keywords: English language; Reading; English language -- Reading -- Study and teaching